Mauritius : Technical Assistance Report-Report on the Price Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations of the IMF mission regarding methodological soundness of all price indexes compiled by the authorities in Mauritius. The methodologies employed by Statistics Mauritius are sound and largely in line with the international guidelines and practices. All price indexes use similar aggregation methodologies and the same index compilation system. Statistics Mauritius is dependent on a consultant to maintain the compilation system. Over time it would be helpful for Statistics Mauritius to explore ways of improving the application of the Statistics Act to acquiring business survey data and administrative data from both government departments and private corporations to improve the coverage and quality of the statistics.